Studi Harmonisa Akibat Komponen Penyearah Pada Gardu Traksi Kereta Rel Listrik (KRL) - Ahmad Zamzami; I Made Ardita Y; Faiz Husnayain (CYCLOTRON, 2020)
The electrification system on the Jabodetabek Electric Train uses a direct current system of 1500 VDC. The 1,500 VDC overhead system is supplied from the traction substation which is equipped with a silicon rectifier component. This rectifier component can produce harmonics that can distort the medium voltage source of 20 kV PLN and in the long run, can cause damage to electrical equipment. This study aims to determine the value of the harmonic voltage and current and to design a harmonic filter on the KRL traction substation. The results of harmonic distortion measurements on 20kV / 1.2kV cubicle at traction substations with PQA show a maximum THD-v of 3.43% (according to IEEE standards) and a maximum THD-i of 94.86%.  The maximum TDD value is 0.73% (according to the IEEE standard), but the 5th, 7th and 11th IHD-i exceed the IEEE standard, with values of 70.04%, 43.38%, and 21.5%. The design of harmonic filters using ETAP 12.6.0 shows the value of THD-i dropped to 0.00%.